2017
DOI: 10.14218/jcth.2017.00054
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Hepatitis: Lost in Translation

Abstract: Alcoholic hepatitis is the most severe and acute form of alcoholic liver disease. The mortality rate associated with alcoholic hepatitis is high, largely due to the lack of suitable pharmacological interventions. While there has been substantial research in the area, generating pharmacological interventions has been plagued by the lack of a robust mouse model both for testing and for understanding the underlying pathology. A number of major notable advances have been made in this area recently, with the goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 99 publications
(142 reference statements)
0
12
0
Order By: Relevance
“…An overwhelming number of patients with excessive alcohol consumption and alcoholic hepatitis present with marked fibrosis 18 . In alcoholic liver disease, the fibrogenic response in the liver after the uptake of alcohol is driven by acetaldehyde.…”
Section: Pathogenesis Of Hepatic Fibrosismentioning
confidence: 99%
“…An overwhelming number of patients with excessive alcohol consumption and alcoholic hepatitis present with marked fibrosis 18 . In alcoholic liver disease, the fibrogenic response in the liver after the uptake of alcohol is driven by acetaldehyde.…”
Section: Pathogenesis Of Hepatic Fibrosismentioning
confidence: 99%
“…In patients with underlying alcoholic cirrhosis, it can present as acute-on-chronic liver failure (ACLF), with very poor prognosis and high mortality in the absence of best medical standard of care or liver transplantation. 1,2 Recommended treatment options for AH, even though beneficial in select patients in the short term, are not without risksuch as sepsis and multiorgan failure with corticosteroid use, rapidly progressive extrahepatic organ failures and high risk of alcohol relapse that foretell poor outcomes with liver transplantation. 3,4 In regions entrenched in complementary and alternative medicine (CAM) medical practices, such as India, the use of alternative systems of medicines, such as Ayurveda, Siddha, Homeopathy, Unani and proprietary herbal drugs for management of acute as well as chronic liver diseases, is on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…These observations largely mirror previous data found in alcoholic hepatitis patients by our own group (5). Further studies are necessary in this area in large, multi-institutional cohorts to validate the potential for cK18-to-K18 ratio or the individual values alone to predict mortality (7). Multiple studies have now confirmed increases in K18 and cK18 in AH patients (5,6).…”
mentioning
confidence: 99%
“…Previous work from our laboratory has noted that K18 levels can increase to as much as 30,000 U/L in the absence of increases in ALT in alcoholic hepatitis (5). As such, while K18 is likely a very good biomarker of liver injury in multiple models, K18 elevations in ACLF patients, especially those with alcoholic hepatitis, may be related to factors other than just cell death (5,7). This hypothesis is further supported by the terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) assay (3,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation